2019
DOI: 10.1088/1755-1315/278/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of the upper-layer seawater properties in the Banda Sea: observed from an autonomous CTD Argo float

Abstract: An autonomous CTD (conductivity-temperature-depth) Argo float was deployed in the deepest Weber Basin of Banda Sea to investigate seasonal changes of the upper-layer seawater properties from the first year of CTD time-series data between August 2017 and July 2018. It is found that the float trajectory formed distinct elliptical-shapes, exhibiting a new picture of deep clockwise circulation of the float parking depth at 1000 m. On seasonal scale, large fluctuation of properties, mixed-layer depth, and thermocli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
4
0
4
Order By: Relevance
“…Kompleksnya topografi dasar lautnya sangat membentuk cekungan di bagian barat dan palung di bagian timur [11]. Laut Banda juga merupakan jalur timur Arlindo (ITF) [2] dan sebagai penampung sementara massa air dari samudera Pasifik menuju Samudera Hindia.…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Kompleksnya topografi dasar lautnya sangat membentuk cekungan di bagian barat dan palung di bagian timur [11]. Laut Banda juga merupakan jalur timur Arlindo (ITF) [2] dan sebagai penampung sementara massa air dari samudera Pasifik menuju Samudera Hindia.…”
Section: Pendahuluanunclassified
“…Arlindo memainkan peran penting dalam mengendalikan ekosistem laut, interaksi lautatmosfer serta variabilitas iklim di laut Indonesia dan kawasan Indo-Pasifik [2,6]. Massa air Arlindo yang masuk ke Indonesia berasal dari pasifik utara dan pasifik selatan [5,7,12].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…This flow has two routes, namely the western route to the North Pacific from the Sulawesi Sea which branches into the Makasar Strait and Maluku Sea, and flows south through the Flores and Banda Seas. The eastern route to the South Pacific flows from the Halmahera Sea, Maluku Sea, and Seram Sea through the Lifamatola pressure and flows into the Banda Sea [3]. If we look at the two ITF routes, it can be indicated that the Maluku Sea is thought to be crossed by two different water masses, namely coming from the North and South Pacific.…”
Section: Introductionmentioning
confidence: 99%